Comparación de las demandas físicas y fisiológicas entre partidos amistosos y diferentes sesiones de entrenamiento del periodo preparatorio en futbolistas profesionales] - Campos-Vazquez, M. A.; Castellano, J.; Toscano-Bendala, F. J.; Owen, A. (Revista Internacional de Ciencias del Deporte, 2019)
The aim of this study was to compare the physical and physiological demands of friendly matches (FM) with different types of standard training sessions (TRs) undertaken by professional soccer players. Maximal velocity (MV), relative distance (m/min), distance covered in different high velocity and acceleration-deceleration zones, player load, repeated high intensity efforts and Edwards` TRIMP were assessed in 15 professional Spanish soccer players across the preseason period. Training sessions were classified under: tactical, pre-match activation, fitness-reserves and fitness sessions. Differences between FM and TRs, were analyzed for practical significance using magnitude-based inferences. MV and relative distance were substantially higher in FM than in tactical sessions (effect size, ES=1.69, large and 3.73, very large), activation sessions (ES=2.07, very large and 2.30, very large), fitness-reserves sessions (ES=2.85, very large and 4.47, very large) and fitness sessions (ES=2.30, very large and 6.30, very large) respectively. No substantial differences were observed in distance covered in high acceleration zone (>3 m·s-2) between FM and activation, fitness-reserves and fitness sessions. TRIMPs obtained during FM were substantially higher than in tactical (ES= 5.37, very large), activation (ES=5.03, very large), fitness-reserves (ES=3.82, very large) and fitness sessions (ES=5.61, very large). It can be concluded from this study that FMs produce the highest loaded training stimulus when compared across most metrics used for training analysis comparisons across the preseason period. As a result the use of FMs within the pre-season phase of the season should warrant additional care when planned between high intensity and high volume training loads.